Linking user experience and consumer-based brand equity: the moderating role of consumer expertise and lifestyle. Issue 4 (18th August 2014) - Mishra, Abhishek; Dash, Satya Bhusan; Cyr, Dianne
Abstract : Purpose: – The study aims to explore the buildup of consumer-based brand equity (CBBE) from positive derived experiences. Rewarding experiences with products make a user feel good about their decision to buy and use them. Those feelings get accrued as strong consumer–brand relationship, measured comprehensively by CBBE in marketing literature. Design/methodology/approach: – The study is conducted in two phases – exploratory and validation. The exploratory phase involved conceiving a theoretical framework from in-depth literature review. The framework is then validated through a survey-based empirical phase. Smartphones form the context of the work. Findings: – The three consumption values used in the study are usability, social value and pleasure in use. Brand equity has been conceptualized and measured as brand association, perceived value, brand trust and brand loyalty. The moderating role of user expertise, as well as lifestyle, was also tested on pleasure derived. Most of the hypothesized relationships between different constructs of experience and brand equity were found significant. Significant evidence for hierarchical formation of brand equity was also established. Research limitations/implications: – Lack of evidence of moderation of lifestyle may be ascribed to the validity of the scale used to measure it in the current context and needs to be updated. The study contributes by conceiving experience as a multidimensional framework based on Holbrook's typology, besides validating its relationship to CBBE. Hierarchical formation of brand equity is also a novel contribution. Practical implications: – This study provides an indicative guide to marketers with design cues that can provide relevant consumption values in the quest for a positive brand impression. It also provides directions for segmenting the smartphone market based on user expertise for better branding. Originality/value: – The study is innovative by relating experience, conceptualized with Holbrook's framework and CBBE – something yet to be seen in the literature.